On the Performance of Code Block Segmentation for LTE-Advanced: An In-Depth Analysis - Lenzi, Karlo; Figueiredo, Felipe A. P.; B. Filho, José A.; Figueiredo, Fabricio L. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2013)
In our previous work, we presented a brief analysis of the performance of the code block segmentation procedure adopted by the 3GPP LTE Advanced Standard as part of its physical layer channel coding scheme. Here, an in-depth analysis of its performance is offered together with a new approach to the LTE-Advanced code block segmentation. Code block segmentation is a generic procedure applied before turbo encoding whose function is to fragment a large transport block into smaller code blocks, reducing memory requirements. Analysis showed that only 39% of all transport blocks need segmentation. Results based on two different architectures, one focused on a DSP and the other on an FPGA, provided a speedup of 80 times over the original procedure with a total resources count of 166 slices, maximum frequency of 392 MHz and with very low latency.